Principal Stability and the Rural Divide - Andrew Pendola; Eward Fuller (Journal of Research in Rural Education, 2018)
This article examines the unique features of the rural school context and how these features are associated with the stability of principals in these schools. Given the small but growing literature on the characteristics of rural principals, this study presents an exploratory analysis of principal stability across schools located in diff erent geographic locales. We use longitudinal data covering all certifi ed education positions in Texas over an eight-year period and employ logistic regression models to examine the ways in which individual and school characteristics infl uence fi ve-year retention rates for all principals as well as for rural principals. Broadly, our data show that rural principals, on average, leave their positions earlier than non-rural principals and have lower levels of stability. Our results further suggest that while rural principals exhibit less gender and racial diversity, they do not exhibit shorter spells of employment as a principal after controlling for personal and school characteristics. Rural female principals are more stable than rural male principals. In addition, we fi nd that principals with more teaching experience are more stable while those with more assistant principal experience are less stable.